Perception of consultants, feedlot owners, and packers regarding management and marketing decisions on feedlots: A national survey in Brazil (Part II) - de Andrade, Thiago Sérgio; Albertini, Tiago Zanett; Barioni, Luís Gustavo; de Medeiros, Sérgio Raposo; Millen, Danilo Domingues [UNESP]; Dos Santos, Antônio Carlos Ramos; Goulart, Rodrigo Silva; Lanna, Dante Pazzanese Duarte (Canadian Science Publishing, 2020)
Research interviews with agribusiness professionals are carried out in several countries for updating and developing technologies. This study aimed to investigate the perception of Brazilian feeders regarding management and marketing tools used in the feedlot industry. Interviews were conducted with groups: nutritionist-consultants (n = 23), feedlot owners (n = 21), and packer-owned feedlots (n = 8). Roughly 58% of the interviewees worked with two cycles of animals per year. Roughly 80% of animals on feedlots were males, with 73% of the respondents having fed only intact males and 75% of the animals were Nellore breed. Among the criteria used for pen formation, weight was the most common (75%). The use of computational tools for feedlot management (71%) and diet formulation (69%) were found to be common, although interviewees did not use any software to characterize feeder animals. In 44% of the respondent feedlots, animals that reached the desired weight and degree of finish were removed for slaughter, whereas the unfinished animals remained in the same pen. We found that a need, therefore, exists to develop efficient strategies for forming homogeneous pens upon animal entry onto feedlots, and maintaining homogenous pens upon the exit of animals for slaughter.
Keywords: Behaviour; Cattle; Farming practices; Feedlot; Management